Persepsi Mahasiswa Terhadap Penggunaan Youtube Dalam Perkuliahan Belajar Pembelajaran Di Perguruan Tinggi - Rachmad Agung Prayogi (FKIP, Universitas Palangka Raya, 2025)
This study aims to explore students' perceptions of students' perceptions of the use of YouTube in learning in higher education. The rapid development of technology, including the YouTube platform, has had a major impact on the education sector, especially in higher education, including the use of platforms in the learning process to support students' academic success. This study uses a qualitative approach using a case study to examine how students of the economics education study program at Tanjungpura University view and utilize the YouTube application in the learning process. The data collected came from 100 students through questionnaires and in-depth interviews. The findings show that the majority of students have a positive perception of the use of the YouTube platform that supports students' academic abilities and enthusiasm for learning. However, some concerns are excessive dependence on technology and the accuracy of information. This study shows that although YouTube can be a good tool in the learning process, it must be integrated into the right pedagogical approach to maximize its role as a tool in the learning process. This study provides insight for educators to optimize technology including the YouTube platform in learning in higher education